The effects of the economic structural adjustment programs on agriculture in Sub Saharan Africa: a case study of Zimbabwe 1990-2000 - Shoko, Ropafadzo (Research of GSB, 2018)
The Zimbabwean economy has been in decline for the past two decades with the economic situation reaching its worst state in 2008. This period was followed by the adoption of a multi-currency regime in 2009, which the Zimbabwean government hoped would lend some stability to the crumbling economy. The agricultural sector, which was previously considered the cornerstone of the economy has been contributing increasingly less and less to the country's gross Domestic Product, with the current state of the sector being the worst it has been since the country's independence in 1980. Much research has been done to establish the source of the decline in the sector with the major findings pointing toward unfavourable weather conditions, the issue of the equitable distribution of land and the IMF and WB mandated Economic Structural Adjustment Program. This research focused on the effects of ESAP on the agricultural sector with a view to highlight the themes that emerged on key indicators over the adjustment period from 1990 to 1995 as well as a period after to 2000 in order to consider the time lagged effects of adjustment policies. In addition to this, this research investigated the extent to which the ESAP policies were applied, and whether this may have been a reason for ESAP's perceived failings. This paper concluded that despite the shortcomings of ESAP, policies recommended pursuant to this program were not the direct source of the decline of the sector, but rather the non or poor implementation of policies as well as the socio-political environment in the country.